THE PROPERTIES OF CADMIUM OXIDE-CARBON NANOTUBE NANOCOMPOSITE SYNTHESIZED VIA SOL-GEL METHOD - Başgöz, Öyküm; Guler, Omer; Albayrak, M. Gökhan; Takgün, Mehmet (My University, 2019)
In this study, cadmium oxide based carbon nanotube reinforced material wasproduced and the optical and electrical properties of the obtained compositewere investigated. After the carbon nanotubes used as reinforcement materialwere synthesized using the chemical vapor deposition method, they weresupplemented at different ratios to the commercially available cadmium oxidepowders. As another group of samples; cadmium oxide powders weresynthesized by the sol-gel method and the carbon nanotubes were againsupplemented at different ratios. Synthesized carbon nanotubes weresubjected to Transmission Electron Microscope examination. Compositematerials obtained were examined by Scanning Electron Microscope. Then,the changes in the electrical conductivity of the composites obtained bytemperature were measured. The optical properties of the composites weredetermined by taking UV-vis spectrometers.
Keywords: Nanobilim ve Nanoteknoloji; Fizik; Katı Hal; Fizik; Atomik ve Moleküler Kimya; Fizikokimya